The Role Of Innovation In Delivering The Influence Of Market Orientation On The Business Performance Of Umkm Leather Craft Shop In Sukaregang - Geryn Winston; Sukma Nugraha; Teten Mohamad Sapril Mubarok (Entrepreneurship Faculty, Universitas Garut, 2025)
This study was conducted in Sukaregang, Garut, West Java, known as a center for the leather craft industry. The main focus of this research is to explore the role of innovation in mediating the relationship between market orientation and business performance of leather craft SMEs. The purpose of this study is to test the hypothesis that explains the relationship between business performance variables influenced by market orientation and mediated by innovation in leather craft SMEs in Sukaregang, Garut. The sample size in this study is 112 units of leather craft SMEs in Sukaregang. The sample was determined using the saturated sampling technique (census). The data analysis technique used is path analysis and Sobel test using SPSS version 24 software. The data collection method used in this study is a survey conducted by distributing questionnaires. The results show that market orientation has a positive but not significant effect on business performance, market orientation has a positive and significant effect on innovation, innovation has a positive and significant effect on business performance, and innovation significantly mediates the effect of market orientation on business performance.